Event-triggered H∞ control of networked switched systems subject to denial-of-service attacks. (November 2020) - Han, Yuchen; Lian, Jie; Huang, Xi
Abstract: This paper investigates the event-triggered H ∞ control of networked switched systems in the presence of Denial-of-Service (DoS) attacks. DoS attacks prevent the sampled information of system state and switching signal from transmitting among the network. The transmission delay on the switching of controller leads to asynchronous switching. By a suitable event-triggered scheme, the bound of the actual DoS-induced transmission delay is obtained, which can be used to construct a merged switching signal combining the switching signal of system with DoS-induced switching signal of controller. The original networked switched systems under DoS attacks can be modeled as new switched systems with this merged switching signal. By constructing multiple quadratic Lyapunov functions with the merged switching signal, some sufficient conditions are provided for event-triggered H ∞ controller. Finally, in order to demonstrate the effectiveness and feasibility of the proposed methods, a numerical simulation is performed.